1997
DOI: 10.1046/j.1523-1739.1997.95485.x
|View full text |Cite
|
Sign up to set email alerts
|

Tests of Null Models for Amphibian Declines on a Tropical Mountain

Abstract: Many of the recent, widespread declines and disappearances of amphibian populations have taken place in seemingly undisturbed, montane habitats. The question of whether the observed patterns differ from those expected from natural population dynamics is the subject of an ongoing controversy with important implications for conservation. We examined this issue for the Monteverde region of Costa Rica’s Cordillera de Tilarán, where a multi‐species population crash in 1987 led to the disappearance of the endemic go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
130
0
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(142 citation statements)
references
References 26 publications
7
130
0
3
Order By: Relevance
“…The decline of amphibians in El Yunque Forest in Puerto Rico is believed to be a consequence of a change in their behavior during dry periods, with populations moving from a dispersed distribution to a few protected microsites on the landscape, increasing their vulnerability to contagion (48). Similar patterns were observed at Monteverde prior to the multispecies population crash and extinction of the golden toad in 1987 (1,9,34,41). Extinction events are an omnipresent feature of the history of life (49).…”
Section: )mentioning
confidence: 80%
See 2 more Smart Citations
“…The decline of amphibians in El Yunque Forest in Puerto Rico is believed to be a consequence of a change in their behavior during dry periods, with populations moving from a dispersed distribution to a few protected microsites on the landscape, increasing their vulnerability to contagion (48). Similar patterns were observed at Monteverde prior to the multispecies population crash and extinction of the golden toad in 1987 (1,9,34,41). Extinction events are an omnipresent feature of the history of life (49).…”
Section: )mentioning
confidence: 80%
“…In that case, warmer Pacific SSTs were interpreted to correspond to warmer, drier conditions in the cloud forest. Based on statistical hypothesis testing, Pounds and coauthors (34) subsequently concluded that the abnormal dry conditions of 1987 were likely to have caused the multispecies population crash, which included the extinction of the Monteverde Golden Toad. Both of these papers speculated at the time that disease may have been the proximate cause of the extinction of the golden toad (9, 34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is not the only agent of declines in this region, the southeastward spread of chytridiomycosis is depleting amphibian populations (Daszak et al, 2003;Lips et al, 2003a). Monitored populations have declined throughout Costa Rica (Pounds et al, 1997; and western Panama, and chytridiomycosis was associated with these events (Berger et al, 1998;Lips, 1999;Lips et al, 2003a).…”
Section: Introductionmentioning
confidence: 99%
“…In Central America, the decimation of highland amphibian populations was first noted in Monteverde, Costa Rica (35,36), in the late 1980s, and since then the spread of B. dendrobatidis has been moving in an epidemic wave from the northwest toward the southeast through the cordillera of Isthmian Central America (9,(37)(38)(39)(40). Anticipating the arrival of B. dendrobatidis, an intensive field survey and monitoring program was established in 1998 in the G. D. Omar Torrijos H. National Park (latitude 08.667, longitude −080.592) at 800 m elevation, near El Copé, Panama (9).…”
mentioning
confidence: 99%